National ocean policy in the United States: using framing theory to highlight policy priorities between presidential administrations - Johnson, Gregory; Anderson, Christopher; Dunning, Kelly; Williamson, Ryan (Frontiers in Marine Science, 2024)
Coastal and ocean management in the United States is a complex issue requiring an equally complex management policy. Federal policy has historically been carried out in a siloed (sector-by-sector) fashion causing inefficient and bureaucratic management by federal agencies. The Obama administration took a novel approach to coastal and ocean management by signing an executive order that brought together federal agencies and empowered regional stakeholders, creating a first of its kind comprehensive National Ocean Policy. In 2018, former President Donald Trump rescinded the Obama-era policy and enacted his own version of National Ocean Policy that shifted authority to the states and focused on the economic potential of American waters. This research addresses a significant challenge in federal management of a complex natural resource. Here we identify common management strategies between different administrations to provide insights for future attempts at National Ocean Policy. We collect policy documents, press releases, and congressional testimony from high-level stakeholders and identified the most common themes over a 12-year period from 2009-2021. We find three common themes between the administrations even though their policies varied in strategy and scope: 1) the importance of a strong and enduring marine economy, 2) creating a strategic and efficient ocean policy, and 3) devolving authority from the federal government to state and regional decision-makers. We argue that coastal and ocean management via executive order is too easily rescinded to have a lasting impact. These novel findings highlight potential strategies for bipartisan cooperation in future attempts at National Ocean Policy.